SUPERVISOR SUPPORT AS A KEY FACTOR IN MEDIATING BURNOUT AGAINST EMPLOYEE TURNOVER INTENTION OF PT. PERINTIS KARYA SENTOSA SEMARANG - Natasha, Sheila; Pudjiarti, Emiliana Sri (STIE Pelita Nusantara Semarang, 2024)
In this current work environment, the role of supervisor support as a mediator in overcoming burnout and its impact on employee turnover intention is the main focus. This research tries to explore the relationship between burnout, job insecurity, and turnover intention, as well as the mediating role of supervisor support. Through research conducted on 80 employees of PT. Perintis Karya Sentosa Semarang, and data is processed using PLS 3.0 software. The research results show that there is a significant negative influence between supervisor support on turnover intention. Furthermore, it was found that job insecurity and burnout had a positive and significant relationship to turnover intention. These results underline the important role of supervisor support as a key factor in mediating the impact of burnout on employee turnover intention.